(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Assamese women of the Ahom era were portrayed by Assamese historians in a highly positive light. Women at that period held a very high social status in their eyes. However, in reality, very negative things are observed. During that period, polygamy was prevalent in both royal and common families. One feature of that culture was slavery. Women were viewed as goods to be bought and sold. They were likened to inanimate objects and animals. The presence of three female rulers of the Ahom period—Phulesvari, Ambika, and Sarbesvari—is the most important aspect of this era. However, they were all the wives of King Sib Shing, who, as a result of his circumstances, had to abdicate his crown. Thus, discussing the political status of Assamese women at that time is pointless. Assamese women continue to be captivated by the historical account of Joymoti Kunwari and Mula Gabhoru’s gallantry and sacrifice.